A new black fly (Diptera: Simuliidae) species of the subgenus Asiosimulium Takaoka & Choochote from Thailand - Tangkawanit, Ubon; Wongpakam, Komgrit; Pramual, Pairot (Zootaxa, 2018)
A new black fly species of the subgenus Asiosimulium Takaoka & Choochote of the genus Simulium was recognized from northeastern Thailand based on morphology, mitochondrial DNA and ecology. This black fly species has similar morphological characteristics to Simulium oblongum Takaoka and Choochote that was also described from the same geographic region in all life stages. However, this new species could be distinguished at the adult stage by coloration of the maxillary palp and in the larval stage by the presence of a pigmented subesophageal ganglion that is lacking in S. oblongum. Genetic distance and phylogenetic analyses based on mitochondrial cytochrome c oxidase I sequences clearly differentiated the two species with minimum genetic distance of 3.51%. These species are also ecologically isolated as S. oblongum is found only at low elevation (<650 m above sea level) but the new species occurs only at high elevation (>1,100 m above sea level).